PEMANFAATAN TANAMAN PENUTUP TANAH DALAM SISTEM USAHA TANI - Kristina Erniyani (Agriculture Faculty of Flores University, 2009)
An intensive agriculture activity, especially that done on dry land, will result in a decrease in productivity. The land will get easily eroted, slopy, sour and poor in nutrition. Sustainable agricultural development needs technologies of conservation of land and water. One of such technologies is the technology of vegetation conservation. This refers to the planting of trees, bush, grass or land covering crops. The planting of land covering crops functions to: 1) minimize erosion; 2) minimize the growth of weeds; 3) change the microclimate and the land temperature; 4) to make sources of livestock food available; 5) increase the land organism; 6) improve the physical and chemical nature of the land. The findings of some researches show that the land covering crops can minimize the speed of erosion 40 %, increase the land fertility by 30 % and minimize the growth of weeds by 50 %.